Psycholinguistic paradigm of the issue of psychological modelling of personal constructs (Actual Problems of Psychology in Educational Institutions, 2022)
The article represents theoretical and methodological review of the positioning phenomenological universals of concepts of language and speech in the dimensions of psycholinguistic science. The historical genesis of the problem allows to indicate the dynamics of scientific views on characteristics of language and speech themselves, which provide social, intellectual and personal functions of a human. It considers the initial theoretical models of generation and development of speech. It is admitted that the use of model representations concerning the logical and semantic organization of speech and thinking activity of the individual is expedient in the psycholinguistic and cognitive paradigms of research.
Keywords: language; speech; linguistic competence; speech competence; modelling; discursive practice; communicative behaviour; psycholinguistics